Non-involuting congenital hemangioma have angioproliferative features of both congenital vascular malformations and of vascular tumors- insights from apoptosis, autophagy and senescence - Utami, Amalia Mulia; Cinkara, Gonca; Pertiwi, Kartika Ratna; Lokhorst, Max M.; de Boer , Onno J.; van der Horst , Chantal MAM; Meijer-Jorna , Lorine B.; van der Wal, Allard C. (Nusantara Medical Science Journal, 2025)
Backgrounds: Non-Involuting Congenital Hemangiomas (NICH) are benign vascular lesions distinguished by the proliferation of micro-vessels. Currently, the underlying pathophysiology and connection with congenital vascular malformations remain uncertain. This study aims to explore age-related discrepancies in NICH and compare them with malformations by examining histological characteristics and assessing markers for cell death, maturation and proliferation. The goal is to ascertain whether NICH should be classified as vascular tumors or vascular malformations, in order to properly classify them within the wide spectrum of vascular anomalies. Methods: Paraffin blocks of 36 clinically documented cases of NICH (n=12) and congenital vascular malformations (n=24) were immunostained using antibodies against cell-death (C-Caspase-3) and cell-cycle related proteins (Ki67, p62, LC3B, p21, p27), and immunodouble stained with smooth muscle actin antibody for identifying immunolocalization with vessel walls. Three independent observers conducted semi-quantitative scoring of stained samples. Statistical analysis was employed to compare differences between NICH in two age groups (young and old), and congenital vascular malformations. Results: Clinical history in combination with histology and Ki67 categorized the lesions into four groups: NICH younger ages (n=7), NICH old ages (n=5), non-proliferative vascular malformations (n=12), and proliferative vascular malformations (n=12). C-Caspase-3 and LC3B showed significantly higher expression in the younger age group of NICH (p<0.05) and proliferative AVM (p<0.05). The senescence marker p21 was elevated only in proliferative AVM, while p27 exhibited higher expression in both NICH and proliferative AVM compared to non-proliferative vascular malformations. Conclusions: This study revealed distinct expression patterns of cell cycle related proteins in different types of benign vascular anomalies and within the same type across different age groups. NICH, despite sharing certain clinical characteristics (onset in utero, no tendency to regress) with congenital vascular malformations, displayed a persistent vasoproliferative behavior and different patterns of apoptosis, autophagy and senescence. These findings may endorse the view that NICH should not be classified as congenital vascular malformations. However, NICH revealed similarities with AVM subtypes harbouring a vasoproliferative component. Therefore, it could be argued whether proliferative components of AVM are really part of the developmental disorder itself , or could represent a (reactive) epiphenomenon.